Effect Of Wheat Bran Substitution For Corn And Dehydrated Alfalfa On Finishing Lambs - Islam, MS; Khan, M; Reza, A (Bangladesh Journal of Animal Science, 2012)
Two trials with finishing lambs were conducted to study the effect of substituting wheat bran for either dehydrated alfalfa pellets or corn. In trial 1, the basal ration fed to lambs was compared by replacing dehydrated alfalfa (12.5%) with wheat bran. Growth responses to wheat bran or dehydrated alfalfa were not different (P>0.74). In trial 2, thirty-two lambs were blocked by weight and randomly assigned to four treatments consisting of the basal ration plus three different levels of wheat bran (22%, 46% and 68%) substituted for corn. The results indicated that animals on the control diet (without wheat bran) performed better (α = 0.5) than the three wheat bran diets, where the two lowest level of wheat bran diet either maintained or gained weight. Animals on the highest level of wheat bran lost weight. Gain response to the corn diet was higher (P<0.25 and P<0.003) than 22% and 46% wheat bran supplemented diets. Results also indicated that diet- A (control) and diet-C (46% wheat bran) had similar DM digestibilities, where as the diet-B (22% wheat bran) gave higher digestibilities for DM, ADF and NDF. ADF digestibility was very low in control diet (A) as compared to diet-B (22% wheat bran) and diet-C (46% wheat bran) because the control diet contained little fiber. Higher protein digestibility was observed in diet-A. Although, diet-B performed better than diet-C, Performance of diet-B was not parallel to that of diet-A and difference between diet-B and diet-C was not statistically significant (P>0.05). DOI: http://dx.doi.org/10.3329/bjas.v38i1-2.9913 BJAS 2009; 38(1-2): 61-66